Gravimetric Study of the Solubility and Dissociation of Benzoic Acid: Effect of Cosolvent and Temperature - Salem Al-Gariri, Hesham Saeed (Universiti Teknologi PETRONAS, 2016)
Solubility study is an important parameter to reach desired concentration of substance especially in pharmaceutical industry. Poorly water soluble crystals may require high doses in order to achieve the required outcome for the process. Benzoic acid (C7H6O2) is widely known as an intermediate for synthesis of several organic substances applied in the fields of pharmaceuticals, resins, plasticizers, dyes and cosmetics. The aqueous solubility of benzoic acid is sparingly low due to its hydrophobic characterstics which is the main issue in this study. This research aims on enhancing the solubility of benzoic acid by using different co-solvents.